Representasi Mewujudkan Ideologi Pancasila dan Prinsip Ajeg Bali pada Tulisan Opini Terbitan Surat Kabar Bali Post (Sebagai Alternatif Pemilihan Materi Pembelajaran Menulis Opini Berbasis Teks) - I Wayan Wendra; Ade Asih Suasiari Tantri (Universitas Mulawarman, 2021)
This study aimed to describe an effort to make Pancasila ideology and Ajeg Bali principle a reality made by Bali Post and opinion contents published in Bali Post daily newspaper. This study was qualitative descriptive research. The data source was opinion articles taken from Bali Post daily newspaper from January to March 2021. The focus of this study was the effort in making Pancasila ideology and Ajeg Bali principle a reality as represented in opinion articles and opinion contents that were published. The data were collected by using a document recording method. The data were analyzed with the inductive method. The results of the study are as follows. The effort to make Pancasila and Ajeg Bali principle become a reality in the publication of opinion articles in Bali Post daily newspaper was made by selecting writers opinions that dealt with various fields of development that were directed toward Indonesia’s national development since they were based on Pancasila ideology and those that were directed toward local development of Bali in particular since the development was based on Ajeg Bali principle. The number of publications that had the national characteristic was 27 (38.57%), and that of those that had the local characteristic was 43 (61.43%) due to the existence of Bali Post daily newspaper as local mass media committed to Ajeg Bali. The selection of the writers’ opinions was based on the qualifications of the opinion writers in their fields., that is, from established academicians and from experienced people in the fields they wrote in. The opinion writers come to form Bali and outside Bali. The fields of the ideas of opinions that were published in Bali Post daily newspaper are consecutive as follows: education 18 (25.71%), cultural art/ custom 15 (21.42%), economics 14 (20%), health 5 (7.14%), tourism 4 (5.71%), agriculture 4 (5.71%), law 4 (5.71%), religion 3 (4.26%), and resources 3 (4.28%). The publications or opinions in Bali Post daily newspaper are consistent with the ideology that it upholds, that is, Pancasila and Ajeg Bali principles. The opinion articles are suitable for use as learning material in opinion writing and analyzing text elements of authentic and contextual opinion texts.